Jumping the fine LINE between species: Horizontal transfer of transposable elements in animals catalyses genome evolution. (3rd September 2013) - Ivancevic, Atma M.; Walsh, Ali M.; Kortschak, R. Daniel; Adelson, David L.
<x xml:space="preserve">Abstract</x> Horizontal transfer (HT) is the transmission of genetic material between non‐mating species, a phenomenon thought to occur rarely in multicellular eukaryotes. However, many transposable elements (TEs) are not only capable of HT, but have frequently jumped between widely divergent species. Here we review and integrate reported cases of HT in retrotransposons of the BovB family, and DNA transposons, over a broad range of animals spanning all continents. Our conclusions challenge the paradigm that HT in vertebrates is restricted to infective long terminal repeat (LTR) retrotransposons or retroviruses. This raises the possibility that other non‐LTR retrotransposons, such as L1 or CR1 elements, believed to be only vertically transmitted, can horizontally transfer between species. Growing evidence indicates that the process of HT is much more general across different TEs and species than previously believed, and that it likely shapes eukaryotic genomes and catalyses genome evolution.